Transfer of Teacher Training: A Case of Teaching Speaking - Adhikari, Ambika Prasad (NUTA Journal, 2018)
The present study entitled ‘Transfer of Teacher Training: A Case of Teaching Speaking’ aims at identifying and describing the teaching activities of trained teachers in terms of motivation, presentation, practice, methods and techniques and evaluation system of teaching and to analyze the transfer of training of trained teachers in teaching speaking skills. This research study shows that training is essential in teaching language especially speaking skills. Trained teachers in most of the cases were found successful in transferring a number of training skills to the classroom delivery.